Музей гетьманства як інформаційний центр з козацько-гетьманської тематики. (Zaporizhzhia Historical Review, 2021)
The activity of one of the centers of Cossackhood research – the Museum of Hetmanship – is being described. The work of this centre in exhibiting and spreading the information about Cossack starshyna is being covered.